2018
DOI: 10.1088/2057-1976/aabeee
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of bioactive glass particle abraded titanium against Streptococcus mutans

Abstract: The purpose of this study was to evaluate effects of titanium surfaces air-abraded with particles of Bioglass® 45S5 and three-ZnO and SrO doped compositions on the viability, adhesion and biofilm formation of Streptococcus mutans. A statistically significant decrease in the viability of S. mutans was observed for all titanium discs air-particle abraded with the BAGs (p<0.001). Also, a significant effect on diminishing biofilm formation on the titanium discs was seen for all BAGs (p<0.01). No differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…BAG-coated dental implants have shown promising results with reduced bone loss in experimentally induced PI in beagle dogs [66]. A recent in vitro study showed reduced biofilm formation of putative periodontal pathogen strains, in addition to S. mutans [67]. Besides, reduced growth of periodontitis-associated and cariogenic bacteria, as well as Enterococcus facials, has been reported using BAG containing propolis, a naturally occurring compound in beehives [68].…”
Section: Properties Of Bioactive Glassmentioning
confidence: 99%
“…BAG-coated dental implants have shown promising results with reduced bone loss in experimentally induced PI in beagle dogs [66]. A recent in vitro study showed reduced biofilm formation of putative periodontal pathogen strains, in addition to S. mutans [67]. Besides, reduced growth of periodontitis-associated and cariogenic bacteria, as well as Enterococcus facials, has been reported using BAG containing propolis, a naturally occurring compound in beehives [68].…”
Section: Properties Of Bioactive Glassmentioning
confidence: 99%
“…Air‐particle abrasion with a bioactive glass has shown an antimicrobial effect and suppressed formation of bacterial biofilm on titanium surfaces in vitro (). The composition of bioactive glass is commonly based on silicon dioxide (SiO 2 )–sodium oxide (Na 2 O)–phosphorus pentoxide (P 2 O 5 )–calcium oxide (CaO) ().…”
mentioning
confidence: 99%
“…Several conventional treatment modalities, including curettes, ultrasonic scalers, and air powder abrasion systems, have been used to detoxify and debride contaminated titanium surfaces. However, these conventional approaches are frequently insufficient to lead to the complete removal of bacterial biofilms from rough implant surfaces (8,9) Air-particle abrasion with a bioactive glass has shown an antimicrobial effect and suppressed formation of bacterial biofilm on titanium surfaces in vitro (10). The composition of bioactive glass is commonly based on silicon dioxide (SiO 2 )-sodium oxide (Na 2 O)-phosphorus pentoxide (P 2 O 5 )-calcium oxide (CaO) (11).…”
mentioning
confidence: 99%
“…As the glass dissolves, these metal ions are released into the interfacial solution at concentrations that induce the desired antibacterial effect. Zinc (Zn) ions are one of the most potent antibacterial elements that inhibit dental plaque pathogens, including Streptococcus mutans, F. nucleatum, and P. gingivalis [27][28][29]. Moreover, the addition of Zn oxide has been found to accelerate bone formation and to enhance BG mechanical properties [30].…”
Section: Introductionmentioning
confidence: 99%